Philippa M. Steele. 2019. Writing and Society in Ancient Cyprus - Iacovou , Maria (Journal of Greek Archaeology, 2019)
Writing and Society in Ancient Cyprus is the edited version of the Evans-Pritchard Lectures, which the author, Philippa Steele (PS), delivered at All Souls College, Oxford, in 2014, under the title, Society and Writing in Ancient Cyprus. The decision to reverse the order of the two main terms on the book’s title suggests that the primacy of Writing over Society had become obvious when the lectures were presented. PS achieved a fascinating synthesis of the written evidence, which would have, undoubtedly, steered her audience towards new venues regarding the interpretation of society in Ancient Cyprus.